On two species of the spider genus Stertinius Simon, 1890 from China (Araneae: Salticidae) - Wang, Cheng; Mi, Xiao-Qi; Irfan, Muhammad; Peng, Xian-Jin (Zootaxa, 2020)
Stertinius Simon, 1890 belongs in the subtribe Simaethina Simon, 1903 of the subfamily Salticinae Blackwall, 1841 (Maddison 2015), which represents a group of small spiders with flatted prosoma and conspicuous, sclerotized sigillae (Logunov et al. 1997; Logunov 2018). Currently, a total of 12 species have been described mainly from East and Southeast Asia, of which five species have only one sex described (World Spider Catalog 2020).